Implantação do serviço de oncologia veterinária no Hospital Veterinário da Universidade Federal de Uberlândia - Santos, Thaisa Reis dos (2018)
As a medical and surgical specialty Veterinary Oncology is growing and stands out nowadays. Taking this into account, the present thesis aimed described the process of design and implementation of Clinical and Oncological Surgery Service - SECCON at Veterinary Hospital of the Federal University of Uberlândia (HV-UFU), according to the standards for manipulation of antineoplastic agents determined by the Brazilian Agency of Sanitary Surveillance (ANVISA). An already existing area of 29 m² was subdivided into five distinct rooms: A - clinical ambulatory; B - antineoplastic chemotherapy administration room; C - cleaning room; D - paramentation room and E - cytotoxic drug manipulation room. In addition, the patient's approach to SECCON was standardized through the creation of a specific clinical record for patients with cancer. SECCON was the first Veterinary Oncology Service in the state of Minas Gerais, as well as a pioneer Oncology Service that followed the technical guidelines of ANVISA's recommended antineoplastic therapy services in a Brazilian University, which allows to conclude that the adequacy of an oncology service legislation for the manipulation of antineoplastic drugs are feasible. Simultaneously with the design and execution of SECCON, a parallel study was conducted with the objective of evaluating risk factors for breast cancer in dogs that were recruited at three consecutive events called "Outubro Rosa Pets", which ones occurred in Uberlândia and Patos de Minas, in 2015, 2016 and 2017. A cross-sectional retrospective study was conducted by analysis of the clinical records filled out during the event of the prevention of breast cancer in bitches. The obtained results reinforce that advanced age, overweight and the failure to perform ovariohysterectomy are considered risk factors related to the presence of breast cancer in bitches and may be associated with the risk to the development of this important neoplasia in dogs.